An overset mesh based multiphase flow solver for water entry problems. (30th August 2018) - Ma, Z.H.; Qian, L.; Martínez-Ferrer, P.J.; Causon, D.M.; Mingham, C.G.; Bai, W.
Highlights: An overset mesh based multiphase flow solver for ship slamming is proposed. The method can handle moving bodies with large amplitude motions in air and waves. The method can successfully avoid non-physical oscillations on solid boundaries. The method can accurately predict the slamming loads on structures. Abstract: This paper extends a recently proposed multi-region based numerical wave tank (Martínez-Ferrer et al. [1]) to solve water entry problems in naval engineering. The original static linking strategy is developed to enable the dynamic coupling of several moving regions. This permits the method to deal with large-amplitude motions for structures slamming into water waves. A background grid and one or more component meshes are firstly generated to overlay the whole computational domain and the sub-domains surrounding the structures, respectively. During computation, the background mesh is fixed while the small grids move freely or as prescribed without deformation and regeneration. This effectively circumvents the large and often excessive error-prone dynamic deformation of a single-block mesh as well as the complex and time-consuming mesh regeneration. Test cases of dam breaking with and without obstacles are first conducted to verify the developed code by comparing the numerical solution against experimental data. Then the new code is used to solve prescribed and free-fall water entry problems. The obtained results agree well with experimental measurements and other computational results reported in the literature.